Chemical Composition, Antioxidant Potential, and Antibacterial Activity of Essential Oil Cones of Tunisian Cupressus sempervirens - Aicha Ben Nouri; Wissal Dhifi; Sana Bellili; Hanene Ghazghazi; Chedia Aouadhi; Ameur Chérif; Mohamed Hammami; Wissem Mnif (Journal of Chemistry)
The extraction yield of the essential oil (EO) extracted by hydrodistillation from the cones of Tunisian Cupressus sempervirens L. was of 0.518%. The chemical composition was analyzed by GC-MS. Results showed that this essential oil was mainly composed of monoterpene hydrocarbons (65%) with α-pinene as the major constituent (47.51%). Its antioxidant activity was ascertained by evaluating the total antioxidant capacity and also by evaluating its inhibitory effect against DPPH and ABTS radicals. In addition, it showed a strong antioxidant power against the DPPH (IC50 = 151 µg/mL) and ABTS (IC50 = 176.454 µg/mL) radicals scavenging. Moreover, its antibacterial activity was tested against different species of pathogenic bacteria (three Gram-positive and eight Gram-negative bacteria). The bacterial strains susceptible to the evaluated oil were Bacillus subtilis, Escherichia coli, Klebsiella oxytoca, Morganella morganii, Shigella, and Vibrio cholerae.